Respuesta :
Step-by-step explanation:
The sequence above is an arithmetic sequence
For an nth term in an arithmetic sequence
A(n) = a + ( n - 1)d
where a is the first term
n is the number of terms
d is the common difference
From the question
a = - 1
To find the common difference subtract the previous term from the next term
We have
d = 4 --1 = 4 + 1 = 5 or 9 - 4 = 5
Therefore d = 5
Substitute the values into the general formula
That's
[tex]A(n) = - 1 + (n - 1)(5) \\ = - 1 + 5n - 5 \\ = 5n - 6 \: \: \: \: \: \: \: \: \: \: \: [/tex]
To find A(50) substitute the value of n that's 50 into the formula above
[tex]A(50) = 5(50) - 6 \\ \: \: \: \: \: \: \: \: \: = 250 - 6 \\ \: = 244[/tex]
Hope this helps you
Step-by-step explanation:
The sequence above is an arithmetic sequence
For an nth term in an arithmetic sequence
- A(n) = a + ( n - 1)d
where a is the first term
n is the number of terms
d is the common difference
From the question
- a = - 1
To find the common difference subtract the previous term from the next term
- d = 4 --1 = 4 + 1 = 5 or 9 - 4 = 5
Therefore d = 5
Substitute the values into the general formula
That's
[tex]A(n)=−1+(n−1)(5) \\ \: \: \: \: \: \: \: \: =−1+5n−5 \\ =5n−6[/tex]
To find A(50) substitute the value of n that's 50 into the formula above
[tex]A(50)=5(50)−6 \\ \: \: \: \: \: \: \: \: =250−6 \\ \: \: =244[/tex]